Acute aortic syndrome. Two-case report and literature review - Guzmán-Del Giudice, Oscar Enrique (2021)
The Acute Aortic Syndrome (ASS) imposes a diagnosis challenge for emergency physicians. Its very variable clinical presentation and poor symptomatic specificity makes it very difficult to diagnose, being the high clinical-suspicion index the clue for attaining it. Aortic dissection is the most common form of AAS,followed by intramural hematoma (IMH) and penetrating aortic ulcer (PAU). Congenital cardiovascular defects, genetic syndromes, and nonsyndromic genetic variants have all been linked with the development of AAS. The diagnosis of AAS in the clinic can be made using imaging modalities such as CT,echocardiography, and MRI. Medical and/or surgical treatment must be provided depending of the compromised aortic segment. We report two cases of AAS received medical care at the Emergency Department of Clínica Delgado during 2015.